اتجاهات طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية نحو تطبيقات الذكاء الاصطناعي دراسة ميدانية في معهد علوم وتقنيات النشاطات البدنية والرياضية - سديرة محمد (My University, 2024)
ملخص الدراسة: عنوان الدراسة:اتجاهات طلبةمعهدعلوم وتقنيات النشاطات البدنية و الرياضية نحو تطبيقات الذكاء الاصطناعي. هدفت الدراسةإلى التعرف على اتجاهات الطلبةالجامعيين نحو استخدام تطبيقات الذكاء الاصطناعي. مشكلة الدراسة:ماهي اتجاهات طلبة المعهدنحوتطبيقات الذكاءالاصطناعي؟ فرضيات الدراسة:هنا كاتجاهات إيجابية اللطلبة المعهد نحو توظيف تطبيقات الذكاء الاصطناعي. وأجريت هذهالدراسة على(60) طالبجامعي وبالضبط طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية بجامعةسوق اهراس. واستخدم الباحث المنهج الوصفي،حيثتم إعداد استبانة،ت كونت من (24) سؤال،وقدتم الاعتمادعلى عدةأساليب إحصائية في معالجة البيانات منها:التكرارات،النسب المئونة،المتوسط الحسابي،الانحراف المعياري. وصلت الدراسةإلى النتائج التالية: للطلبة معهدعلوم وتقنيات النشاطات البدنية والرياضية اتجاه اجابي نحو توظيف تطبيقات الذكاءالاصطناعي في مجال التعلم والبحث العلمي وهذا راجع للتوفر مسببا تذلك حيث جلهميم تلكونهواتفذكيةوتحكم جيد في التكنولوجيات الحديثة والاتصال الدائم بالأنترنت. Abstract : Title of the study: Attitudes of students of the Institute of Physical Activity Science and Technology towards artificial intelligence applications. The study aimed to identify the attitudes of university students towards the use of artificial intelligence applications. Problem of the study: What are the attitudes of the institute's students towards artificial intelligence applications? Hypotheses of the study: There are positive attitudes of institute students towards the use of artificial intelligence applications. This study was conducted on (60) university students, specifically students of the Institute of Sciences and Technologies of Physical and Sports Activities at Souk Ahras University. The researcher used the descriptive method, where a questionnaire was prepared, consisting of (24) questions, and several statistical methods were used to process the data, including: Frequencies, percentages, arithmetic mean, and standard deviation. The study reached the following results: Students at the Institute of Science and Technology of Physical Activities and Sports have a positive attitude towards the use of artificial intelligence applications in the field of learning and scientific research due to the availability of the reasons for this, as most of them own smart phones, good control of modern technologies and permanent connection to the Internet. résumé : Titre de l'étude : Attitudes des étudiants de l'Institut des Sciences et Technologies des Activités Physiques et Sportives envers les applications de l'intelligence artificielle. L’étude visait à identifier les attitudes des étudiants universitaires à l’égard de l’utilisation des applications d’intelligence artificielle. La problématique de l’étude : quelles sont les attitudes des étudiants de l’institut à l’égard des applications de l’intelligence artificielle ? Hypothèses d’étude : Il existe des tendances positives chez les étudiants de l’institut vers l’utilisation d’applications d’intelligence artificielle. Cette étude a été menée auprès de (60) étudiants universitaires, notamment des étudiants de l’Institut des Sciences et Technologies des Activités Physiques et Sportives de l’Université de Souk Ahras. Le chercheur a utilisé l'approche descriptive, où un questionnaire a été préparé, composé de (24) questions. Plusieurs méthodes statistiques ont été utilisées pour traiter les données, notamment : les fréquences, les pourcentages, la moyenne arithmétique et l'écart type. L'étude a abouti aux résultats suivants : Les étudiants de l'Institut des Sciences et Technologies des Activités Physiques et Sportives ont une tendance positive à utiliser des applications de l'intelligence artificielle dans le domaine de l'apprentissage et de la recherche scientifique, et cela est dû à la disponibilité des raisons pour cela, car la plupart d'entre eux l'ont fait. Téléphones intelligents, bonne maîtrise des technologies modernes et connexion constante à Internet.
Keywords: الاتجاهات; الطالب; الذكاء الاصطناعي; Direction; requester; Artificial intelligence; demandeur; L'intelligence artificielle